Modernity's Mist : British Romanticism and the Poetics of Anticipation - Rohrbach, Emily (Book collections on Project MUSE., 2016)
"Modernity's Mist explores an understudied aspect of Romanticism: its future-oriented poetics. In the work of John Keats, Jane Austen, Lord Byron, and William Hazlitt, Modernity's Mist describes a poetics of future anteriority or the uncertainty of "what will have been"--a grammar of historical engagement for a time of unprecedented political change"--